1-1-04. Positive rate of giant somatosensory evoked potential (giant SEP) and C reflex in benign adult familial myoclonus epilepsy (BAFME). Issue 6 (June 2017) - Hitomi, Takefumi; Kobayashi, Katsuya; Murai, Tomohiko; Sakurai, Takeyo; Matsumoto, Riki; Takahashi, Ryosuke; Ikeda, Akio
Abstract : Benign adult familial myoclonus epilepsy (BAFME) manifests an autosomal dominant trait, cortical tremor resembling essential tremor and infrequent generalized tonic-clonic seizures. BAFME also shows electrophysiological features of cortical reflex myoclonus. To clarify the positive rate of giant somatosensory evoked potential (giant SEP) and C reflex in BAFME, we retrospectively analyzed 19 patients in a total of 14 families (5 men and 14 women, age: 51 ± 16 years) about positive rate of giant SEP and C reflex. The positive rates of giant SEP and C reflex were 17/19 (89%) and 16/18 (88%), respectively. Relatively young 3 patients (27, 30, and 34 years old) showed no giant SEP or no C reflex. 1 patient (34 years old) showed neither giant SEP nor C reflex, who was examined within 1 year from the clinical onset. Whereas even 1 patient without cortical tremor showed giant SEP. The positive rate of giant SEP and C reflex is quite high in BAFME. Even presymptomatic patient showed giant SEP. However, some younger patients did not show giant SEP and/or C reflex. Therefore, family history of both clinical and electrophysiological findings is crucial for the diagnosis of BAFME.